Effect of Olive Oil Back Massage on Selected Fetomaternal Parameters and Maternal Satisfaction Among Primigravid Women During the First Stage of Labour: A Quasi-Experimental Study - Mekala Moorthy (Journal Of Nursing Practice, 2026)
Background: Labour is a physiological process characterised by progressive cervical dilatation, regular uterine contractions, and fetal descent. Although childbirth is a natural process, many women experience pain, anxiety, and physical discomfort during the first stage of labour. Massage is widely used as a non-pharmacological intervention to promote comfort during labour. However, limited evidence is available regarding the effect of olive oil back massage on fetomaternal physiological parameters and maternal satisfaction. Purpose: To evaluate the effect of olive oil back massage on selected fetomaternal parameters and maternal satisfaction among primigravid women during the first stage of labour. Methods: A quantitative study with a quasi-experimental pretest-posttest control group design was conducted among 60 primigravid women admitted to the labour room of Kasturba Memorial Hospital, Dindigul, Tamil Nadu, India. Participants were selected using purposive sampling and allocated to an experimental group (n = 30) and a control group (n = 30). Women in the experimental group received olive oil back massage during the active first stage of labour in addition to routine intrapartum care, while those in the control group received routine care alone. Results: Women who received olive oil back massage had significantly longer uterine contraction duration than those who received routine care (63.00 ± 8.70 vs. 57.50 ± 7.82 seconds; p < 0.05). A significant difference was also observed in uterine contraction frequency between the groups. No significant differences were found in fetal heart rate, systolic blood pressure, or diastolic blood pressure. Among women in the experimental group, 66.7% reported adequate satisfaction and 33.3% reported moderate satisfaction. Conclusion: Olive oil back massage was associated with favourable uterine contraction characteristics without adverse effects on maternal or fetal physiological parameters. The intervention was well accepted by the participants and may be considered a simple, low-cost complementary nursing intervention during the first stage of labour.